New business: Have you done your homework? - Carvalho, João M. S. (Revista Hipótese, 2017)
This paper intends to present a new business canvas that can help entrepreneurs doing their homework before starting a new venture. The Basic Business Creation Model (BBCM) acts like an acid test validating or not the new idea. It can be used as a pedagogical tool as well as a first approach to a new project. With a few steps it is possible to structure the business and assess its economic viability. More, the model makes the entrepreneur decide and act based on a strategic reflection upon the critical factors to be succeeded, and it develops a new insight about the value model that underlies any business.